4 - Comment l’université sénégalaise se territorialise : modalités d’une cohabitation dynamique - Jean Alain Goudiaby, (Journal of Higher Education in Africa, 2012)
With the independences, a major intellectual excitement has gripped several African countries with the idea that their universities have to carry the seeds of self-determination, and from there, they could not isolate themselves from the rest of society. The links between universities and their territories have their premises here. However, it remained to find the terms of this articula- tion. Based on the example of Senegal, we analyze the dynamic coexistence between academic centers and economic areas. It sets up testing grounds of a joint construction space of education, of the research and even produc- tion. In fact, the Senegalese universities incorporate the territories (whether geographical, economic or symbolic) in their current process of construc- tion, allowing for new developments in research and structuring curriculum.